IVIG regulates the survival of human but not mouse neutrophils - Christoph Schneider (Nature Portfolio, 2017)
Abstract Intravenous immunoglobulin (IVIG) are purified IgG preparations made from the pooled plasma from thousands of healthy donors and are being tested in preclinical mouse models. Inherent challenges, however, are the pluripotency of IVIG and its xenogeneicity in animals. IVIG can alter the viability of human neutrophils via agonistic antibodies to Fas and Siglec-9. In this study, we compared the effects of IVIG on human and mouse neutrophils using different death assays. Different commercial IVIG preparations similarly induced cytokine-dependent death in human neutrophils, whereas they had no effects on the survival of either peripheral blood or bone marrow neutrophils from C57BL/6 or BALB/c mice. F(ab’)2 but not Fc fragments of IVIG induced death of human neutrophils, whereas neither of these IVIG fragments, nor agonistic monoclonal antibodies to human Fas or Siglec-9 affected the viability of mouse neutrophils. Pooled mouse IgG, which exhibited a different immunoprofile compared to IVIG, also had no effect on mouse cells. Together, these observations demonstrate that effects of IVIG on neutrophil survival are not adequately reflected in current mouse models, despite the key role of these cells in human inflammatory and autoimmune diseases.